The Show @ UMAG : A Group Exhibition - University of Malaya, Art Gallery (2019)
By: Hakim Zulkifli, Anisa Tajul, Syafiqah Ashri, Farid Khir, Ammar Shaufi, Emiliya Zainal, Haris Hilmi hasram, Luqman Zainal, Hakim Ibnu Rahman, Meor Masri, Mierakamsano, Zakwan Mohd Noor, Isa Ishak, Sorfina A.K., Dhana Aras, Nik Afi Azlam, Fuji Anggara, Hafizuddin Mat Yashim, Aus Firdaus Yusof, Paeh Md Zid, Dhia Afiq Hamran, Amirul Md Noor. Date: 2 May-15 June 2019. Venue: University of Malaya Art Gallery.